Financing development or developing finance? A review of development impact evaluation systems used by development finance institutions in South Africa - Garikayi, Francis Valentine (Graduate School of Business (GSB), 2019)
The landscape of South African National Development Finance Institutions (DFIs) is comprised of twelve entities. Their institutional objectives range from supporting farmers, financing industrialisation, infrastructural development, and promoting financial inclusion. These DFI objectives fall under the umbrella of Private Sector Development (PSD) interventions. Literature established that the success of PSD is contingent on effective impact evaluation. Consequently, the main research question explored in this dissertation is: In what ways, and using what tools and systems, do South African DFIs measure the development impact of their investments? In support of the main question, two sub-questions were are also investigated. Firstly, whether impact evaluation systems provide credible, timely and relevant information. Secondly, whether impact evaluation systems support evidence-based decision making and learning. In response to these questions, a qualitative case study of six National DFIs was carried out. Semi-structured interviews were conducted with DFI staff members involved in impact evaluation. This was supported by secondary data from annual reports and organisational websites. It was established that, firstly, DFIs use non-uniform impact evaluation systems and tools to measure the impact of their investments. Secondly, the systems lack qualitative detail and focus on measuring outputs instead of outcomes. Thus, much emphasis is placed on monitoring instead of impact evaluation. This renders the impact evaluation systems and tools highly ineffective. Finally, whilst the avowed objective of DFIs is development, financial viability takes precedence when selecting projects. Therefore, an emerging conclusion was that systems in place do not support development impact evidence-based decision-making. These findings generated recommendations for changing the development impact evaluation tools and systems used by South African National DFIs. It is expected that recommended changes will maximise DFI socio-economic benefits.